2020
DOI: 10.1002/jat.4102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mycotoxin metabolite de‐epoxy‐deoxynivalenol (DOM‐1) on embryo development and sperm motility in cattle

Abstract: Contamination of animal feed with Fusarium spp results in accumulation of mycotoxins including deoxynivalenol. In animals, deoxynivalenol is metabolized to de‐epoxy deoxynivalenol (DOM‐1), which is generally considered to be a non‐toxic metabolite; however, recent studies demonstrated that DOM‐1 can reduce steroid production and induce apoptosis in the bovine ovary. The objectives of this study were to assess the effects of DOM‐1 on applied aspects of reproductive function in cattle, specifically sperm functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Reproductive studies in dairy cattle are scarce, especially those performed in the field or in in vivo controlled experimental trials with realistic contamination levels of mycotoxins (Table 3). When cows were exposed to DOM-1 via intrafollicular injection (100 ng/mL), a decrease in the follicular development was observed [173]. These authors also exposed cows to DON via feed (3 or 6 ppm) and detected serum levels of DOM-1 10 to 20 times higher than those of DON, reaching 10 to 20 ng/mL.…”
Section: Effect Of Fusarium Toxins On Reproductive System 101 In Vivo...mentioning
confidence: 94%
“…Reproductive studies in dairy cattle are scarce, especially those performed in the field or in in vivo controlled experimental trials with realistic contamination levels of mycotoxins (Table 3). When cows were exposed to DOM-1 via intrafollicular injection (100 ng/mL), a decrease in the follicular development was observed [173]. These authors also exposed cows to DON via feed (3 or 6 ppm) and detected serum levels of DOM-1 10 to 20 times higher than those of DON, reaching 10 to 20 ng/mL.…”
Section: Effect Of Fusarium Toxins On Reproductive System 101 In Vivo...mentioning
confidence: 94%
“…The reduced pregnancy rates are associated with the negative effects of mycotoxins which are possibly attributable to a toxic mechanism (Duffield, 2000;Minervini et al, 2001). Guerrero-Netro et al (2020) studied the effect of naturally contaminated feed on superovulatory response in cows and found that 6 ppm DON did not alter the number of viable embryos recovered on day 7 but de-epoxy deoxynivalenol (DOM-1) reduced the motility of spermatozoa in vitro. Moreover, Yousef et al (2017) reported that ZEA disrupted the normal interaction between sperm and bovine oviductal epithelial cells, hence negatively affecting sperm survival.…”
Section: Discussionmentioning
confidence: 99%
“…The mycotoxin metabolite DOM-1 is generally considered to be relatively inert but has been shown to be active in the ovary and intestine [ 20 , 21 , 22 ]. As DOM-1 lacks the epoxy group necessary for initiating the RSR, the mechanism of action of DOM-1 was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminants are resistant to the toxic effects of DON as most ingested DON is metabolized in the rumen to de-epoxy-DON (DOM-1) [ 16 ], which is considerably less toxic than DON and does not activate the RSR [ 17 , 18 , 19 ]. However, DOM-1 is not inert; it has been shown to increase the immune response in pigs in vivo [ 20 ], to decrease follicle development in vivo in cattle [ 21 ], and to increase apoptosis of bovine ovarian theca cells in vitro [ 22 ]. The mechanism of action of DOM-1 is unclear, as although it stimulated EIF2AK2 and MAPK3/1 phosphorylation in theca cells, it also stimulated the expression of the endoplasmic reticulum stress marker ATF4 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%